GENERAL PROTEOLYTIC ACTIVITY OF PANCREAS TISSUES AT BURN DISEASE - Kharchenko, S.V. (World of Medicine and Biology, 2016)
General proteolytic activity in pancreas tissues of the rats is decreased at the 1 day and the 7 day after burn under conditions of burn disease, compared with the control.